Effect of wire electrode discharge machining process parameters on the surface roughness, hardness, and microstructure of the high carbon steels. (2021) - Rao, Muralidhara; Vijayan, Vijeesh; Anil, Athul; Rai, Prithvi Kumar; Jain, Nirmith R.
Abstract: This paper investigates the effect of wire electrode discharge (WEDM) machining process on the pearlitic steel and subsequently on the surface hardness and roughness respectively. The variation in the WEDM parameters such as pulse current, pulse on-time on the microstructure and recast layer of hard steel was studied using an optical microscope. The effect of recast layer on the surface roughness was evaluated using a surface profilometer. The response of the steel towards pointed indentation before and after the cutting was recorded using a micro hardness tester. According to the results, the WEDM has a profound effect on the recast layer thickness and profile. The recast layer size varied between 16 and 25 μm with as the pulse current and pulse-on time was varied between 10 and 27.5 A and 20–80 ms. Subsequently, the roughness of the machined surface increased from 2.4 to 4.2 μm. An increase in the hardness from the core of the steel to the cut surface recast layer was observed because of thermal gradient in the material due to WEDM.